Optimization Of Handcycle Design And Engineering Using The VDI 2221 Method Through An Anthropometric Approach For The Disabled - Arifiansah, Arifiansah; Anwar, Sahrul (SEAN Institute, 2024)
People with disabilities are people who experience physical limitations either due to birth or accidents and so on, causing difficulty in walking and other activities. One of the obstacles for them is the existence of transportation to do work or just for daily mobility. And one solution to help people with disabilities in doing daily activities is a handcycle. Handcycle is driven by the arms, not the legs. Handcycle is generally used by people with disabilities who have limitations in using their legs. The research activity aims to produce a handcycle product that is friendly to people with disabilities with an anthropometric aspect approach where the bicycle can be moved either manually or electrically. The position of the seat and steering system can be adjusted according to needs. The seat arrangement (adjustable chair) and steering wheel arrangement (adjustable steering wheel) need to be planned in order to provide a sense of security and comfort to the user. The creation of this bicycle product design begins with identifying customer needs, designing a design concept, designing a shape, designing details and making the product. Where Product Design using the VDI 2221 method. A design method that uses a systematic approach to designing products and engineering systems. Through testing of handcycle products carried out by 2 people (users) with disabilities, it shows that users can adjust the distance of the body with the electric steering system and manual steering by adjusting the distance between the seat and steering wheel. The distance between the seat and the electric steering wheel is 726 - 838 (mm), the distance between the seat and manual steering wheel is 675 - 785 (mm), the height of the seat from the floor is 550 - 700 (mm) with a vehicle speed of 25 km/h if using an electric motor.